Effect of methanol extract of cloves (Syzigium aromaticum) on Protein Gene Product 9.5 in the testes of rats (Rattus norvegicus) with induced cryptorchidism - Nufus, Faizah Zakiyyatun; Bambang Sektiari Lukiswanto; Ira Sari Yudaniyanti; Nove Hidajati; Eduardus Bimo Aksono Herupradoto; Budi Utomo (Universitas Airlangga, 2024)
This study aimed to know the effect of cloves (Syzigium aromaticum) methanol extracts as an antioxidant on the germ cells of white rats (Rattus norvegicus) with induced cryptorchidism. The subjects of this study were 24 male white rats aged 21 days, who were divided into six groups. Rats were adapted for 5 days, after which cryptorchidism were induced. Cloves extract was given for 18 days and 36 days. On day-19 and day-37, rats were sacrificed and testicles were taken for Protein Gene Product (PGP) 9.5 detection by immunohistochemistry. These groups consisted of negative control group (given distilled water and sham surgery), positive control group (induction of cryptorchidism and given distilled water), and T treatment group (induction of cryptorchidism and given 70mg/kg bw cloves extract. Kruskal-Wallis test indicated a significant difference (p <0.05). The differences between treatments were shown based on the outcome of the Mann-Whitney test. Cloves acted as an antioxidant for cryptorchid testicular germ cells. It could be concluded that administering methanol extract of clove flowers could ameliorate the expression of PGP 9.5 in the testicular germ cells of white rats in a model of unilateral cryptorchidism.